How frequent are snakebites in Champone district, Savannakhet province in Laos? A cross-sectional survey - Jörg Blessmann (2015)
Background The incidence of snakebites is high in countries with warm climate and where agricultural activities are the main source of income. These characteristics apply to Laos, a landlocked country in Southeast Asia. There are no data on the incidence of snakebites in Laos so far, and this survey aims for providing data on the frequency of snakebites in a district of the southern province Savannakhet. Methodology A cross-sectional study was performed in Champone district, Savannakhet province to estimate the snakebite incidence in this region. Multistage cluster random sampling was applied. In the first stage 61 out of the total of 162 villages in Champone district were randomly selected. In the second stage one third of all households in each of the 61 villages were randomly chosen. One adult household member of each household was asked, whether a family member was bitten by a snake in the last 12 months. Results Thirty-five of 9856 interviewees reported a snakebite in the last 12 months. The estimated incidence of snakebites is 355/100,000 person per year (95% CI 254-495). The incidence is significantly higher in villages located in forested areas than in agricultural areas, 683/100,000 (95% CI 458 – 1012) and 161/100,000 (95% CI 83 - 301) respectively, with a Risk Ratio of 4.2 (95% CI 2.0 – 8.8). All snakebite victims were treated by traditional healers or by self-treatment at home. Nobody went for treatment to a hospital. In contrast to the result of the household survey in Champone district, the district hospital statistics reported only 1 snakebite patient treated in the hospital in 2012. Conclusions Incidence of snakebites is high in the rural district Champone, particularly in forested areas. There is a huge gap between the number of snakebites found during the community survey and the number of snakebites documented in Champone district hospital statistics, because the majority of snakebite victims are treated by traditional healers or by self-treatment in their village. This is a reasonable choice because treatment options in the provincial and district hospitals are limited and snake antivenom is not available so far. There is an urgent need to train hospital staff in assessment and treatment of venomous snakebites and to make antivenom available in provincial and district hospitals in order to tackle this underestimated and neglected public health problem.